Effect of ten-valent pneumococcal conjugate vaccine introduction on pneumococcal carriage in Fiji: results from four annual cross-sectional carriage surveys. Issue 12 (December 2018) - Dunne, Eileen M; Satzke, Catherine; Ratu, Felisita T; Neal, Eleanor F G; Boelsen, Laura K; Matanitobua, Silivia; Pell, Casey L; Nation, Monica L; Ortika, Belinda D; Reyburn, Rita; Jenkins, Kylie; Nguyen, Cattram; et al.
Summary: Background: The indirect effects of pneumococcal conjugate vaccines (PCVs) are mediated through reductions in carriage of vaccine serotypes. Data on PCVs in Asia and the Pacific are scarce. Fiji introduced the ten-valent PCV (PCV10) in 2012, with a schedule consisting of three priming doses at 6, 10, and 14 weeks of age and no booster dose (3 + 0 schedule) without catch-up. We investigated the effects of PCV10 introduction using cross-sectional nasopharyngeal carriage surveys. Methods: We did four annual carriage surveys (one pre-PCV10 and three post-PCV10) in the greater Suva area in Fiji, during 2012–15, of 5–8-week-old infants, 12–23-month-old children, 2–6-year-old children, and their caregivers (total of 8109 participants). Eligible participants were of appropriate age, had axillary temperature lower than 37°C, and had lived in the community for at least 3 consecutive months. We used purposive quota sampling to ensure a proper representation of the Fiji population. Pneumococci were detected by real-time quantitative PCR, and molecular serotyping was done with microarray. Findings: 3 years after PCV10 introduction, vaccine-serotype carriage prevalence declined, with adjusted prevalences (2015 vs 2012) of 0·56 (95% CI 0·34–0·93) in 5–8-week-old infants, 0·34 (0·23–0·49) in 12–23-month-olds, 0·47 (0·34–0·66) in 2–6-year-olds, and 0·43 (0·13–1·42) in caregivers. Reductions in PCV10 serotype carriage were evident in both main ethnic groups in Fiji; however, carriage of non-PCV10 serotypes increased in Indigenous Fijian infants and children. Density of PCV10 serotypes and non-PCV10 serotypes was lower in PCV10-vaccinated children aged 12–23 months than in PCV10-unvaccinated children of the same age group (PCV10 serotypes −0·56 [95% CI −0·98 to −0·15], p=0·0077; non-PCV10 serotypes −0·29 [–0·57 to −0·02], p=0·0334). Interpretation: Direct and indirect effects on pneumococcal carriage post-PCV10 are likely to result in reductions in pneumococcal disease, including in infants too young to be vaccinated. Serotype replacement in carriage in Fijian children, particularly Indigenous children, warrants further monitoring. Observed changes in pneumococcal density might be temporal rather than vaccine related. Funding: Department of Foreign Affairs and Trade of the Australian Government through the Fiji Health Sector Support Program; Victorian Government's Operational Infrastructure Support Program; Bill & Melinda Gates Foundation.